2008
DOI: 10.1534/genetics.108.091553
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal Regulation of the Proliferation vs. Meiotic Entry Decision in the Caenorhabditis elegans Germ Line

Abstract: Reproductive fitness in many animals relies upon a tight balance between the number of cells that proliferate in the germ line and the number of cells that enter meiosis and differentiate as gametes. In the Caenorhabditis elegans germ line, the GLP-1/Notch signaling pathway controls this balance between proliferation and meiotic entry. Here we describe the identification of the proteasome as an additional regulator of this balance. We show that a decrease in proteasome activity, through either genetic mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…5), showed similar expression in the somatic gonad and additional weak expression in the vulva, muscle, and epidermis, suggesting somatic roles for the motif pair. Expression of the WT reporter in the germline itself along the gonad supports its role in the regulation of meiotic entry decision (Macdonald et al 2008) and gametogenesis. This experimental evidence is in full agreement with our computational findings, which showed enrichment of the motif pair in promoters of genes that are germline-and oogenesis-specific, and that are expressed mainly in L4 and adult hermaphrodites.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…5), showed similar expression in the somatic gonad and additional weak expression in the vulva, muscle, and epidermis, suggesting somatic roles for the motif pair. Expression of the WT reporter in the germline itself along the gonad supports its role in the regulation of meiotic entry decision (Macdonald et al 2008) and gametogenesis. This experimental evidence is in full agreement with our computational findings, which showed enrichment of the motif pair in promoters of genes that are germline-and oogenesis-specific, and that are expressed mainly in L4 and adult hermaphrodites.…”
Section: Discussionmentioning
confidence: 77%
“…pas-5 encodes a proteasome subunit alpha type-5 and has been recently shown to have a role in maintaining the balance between proliferation and meiotic entry in the C. elegans germline as well as somatic functions (Macdonald et al 2008). Previous in situ hybridization analysis showed pas-5 mRNA accumulation in the germline (Y. Kohara, NEXTDB; http://nematode.lab.nig.ac.jp/db2/ ShowCloneInfo.php?clone=479g6).…”
Section: Analysis Of the Motif Pair In Transgenic Wormsmentioning
confidence: 99%
“…Recently, protein degradation has also been implicated in regulating mammalian stem cell pluripotency and selfrenewal (Buckley et al, 2012). We previously found that a reduction in proteasome function enhances overproliferation of stem cells in the C. elegans germ line (MacDonald et al, 2008), suggesting that a role for the proteasome in regulating stem cell proliferation might be conserved.…”
Section: Introductionmentioning
confidence: 97%
“…For example, disruption of the polyubiquitin Ubb in mice leads to infertility with a germ cell arrest at the prophase stage of meiosis I (Ryu et al, 2008). In C. elegans, silencing of the genes encoding PBS-4 and PAS-5, two subunits of the catalytic core of the proteasome, results in impaired entry into meiosis (Macdonald et al, 2008). Furthermore, defects in E3 ubiquitin ligases can cause aberrant meiocyte development.…”
Section: Introductionmentioning
confidence: 99%